2012
DOI: 10.7183/0002-7316.77.2.351
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering Paleoarchaic Mobility in the Central Great Basin

Abstract: Analyzing technological patterns and source provenance of stone tools, Jones, Beck, Jones, and Hughes (2003) argue that Paleoarchuic groups of the central Great Basin moved within an extensive home range, perhaps reaching 400 km in its longest dimension. The Eastern Conveyance Zone, as they refer to this territory, was aligned with the predominantly north-south trending mountains and valleys of the province. To evaluate this model of mobility, artifacts were collected from the southern part of the Eastern Conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Even with the reduced size of the Paleoarchaic settlement systems proposed by these researchers (Smith, 2010;Beck and Jones, 2011;Jones et al, 2012), they are still more than 10 times larger than the largest systems observed in the worldwide ethnographic record (Kelly, 2011). The reliance on wetland plants, birds, fish, and small mammals also indicates that high levels of mobility would make little sense, as these resources would be difficult to deplete from a local basin.…”
Section: Prehistoric Contextmentioning
confidence: 95%
See 1 more Smart Citation
“…Even with the reduced size of the Paleoarchaic settlement systems proposed by these researchers (Smith, 2010;Beck and Jones, 2011;Jones et al, 2012), they are still more than 10 times larger than the largest systems observed in the worldwide ethnographic record (Kelly, 2011). The reliance on wetland plants, birds, fish, and small mammals also indicates that high levels of mobility would make little sense, as these resources would be difficult to deplete from a local basin.…”
Section: Prehistoric Contextmentioning
confidence: 95%
“…All three cover extremely large territories, ranging between 46,000 and 107,000 km 2 , extending from the northern Nevada border down to the central and southcentral portions of the state. Smith's (2010) more recent analysis of data from northwestern Nevada found that the Jones et al (2003) reconstructions were much too large (see also Beck and Jones, 2011;Jones et al, 2012). He suggests a conveyance zone less than half the size of what Jones et al (2003) estimated.…”
Section: Prehistoric Contextmentioning
confidence: 98%
“…We are interested particularly in determining if they are locally derived and generally lesser-quality materials, or if they are higher-quality exotics derived from afar. Lesser-quality, local materials are often the result of ad hoc, opportunistic replacement of tools preferentially made from higher-quality, more desirable sources (Jones et al 2012:354; Tankersley 1990:274). Alternatively, the consistent presence of exotic, high-quality resources within a supply zone is more likely to represent the convenient discard of more widely ranging treks, personal in-migration, or long-distance exchange (Amick 2017:131, 133).…”
Section: Mobility and Lithic Supplymentioning
confidence: 99%
“…The archaeological record of the northern Great Basin largely mirrors that of the broader Great Basin. WST lithic toolkits across the Great Basin provide evidence for highly mobile land-use strategies (Graf 2001;Jones et al 2003Jones et al , 2012Smith 2011). Blood protein residue analysis of a WST projectile from western Utah and two handstones from Paisley Caves provide evidence for hunting of Proboscidean and Equus prey (Duke 2015;Jenkins et al 2013).…”
Section: Introductionmentioning
confidence: 99%